If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -22 = -5(x + -6) Reorder the terms: -22 + 8x = -5(x + -6) Reorder the terms: -22 + 8x = -5(-6 + x) -22 + 8x = (-6 * -5 + x * -5) -22 + 8x = (30 + -5x) Solving -22 + 8x = 30 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -22 + 8x + 5x = 30 + -5x + 5x Combine like terms: 8x + 5x = 13x -22 + 13x = 30 + -5x + 5x Combine like terms: -5x + 5x = 0 -22 + 13x = 30 + 0 -22 + 13x = 30 Add '22' to each side of the equation. -22 + 22 + 13x = 30 + 22 Combine like terms: -22 + 22 = 0 0 + 13x = 30 + 22 13x = 30 + 22 Combine like terms: 30 + 22 = 52 13x = 52 Divide each side by '13'. x = 4 Simplifying x = 4
| x*15-180=x*6-9 | | 3(v+1)=-2v-32 | | -3t(2t-5)+4t=5t-9 | | 2x(x+1)-(x+1)=0 | | -.02k+1=11 | | 12s=89 | | 6+49x=21x+42 | | 2x+(x+12)=180 | | .02k+1=11 | | 9(x-2)=3(x-2) | | 4.5x-39=2.2x+7 | | n+n+m=2 | | -3t(4t-4)+8t=3t-4 | | 7x+4=x+10 | | x=y/6(16-z) | | -27x^2+48x-5= | | 4(t-3)=2t+7 | | -2(3t-4)+3t=2t-3 | | -27x^3+48x-5= | | 10x^2+2.5x-45=0 | | 3x+11=6x-4 | | 5+6=5+x | | 6x^2-4x=-11 | | 8+y=6+2y | | -5(3t-2)+2t=4t-9 | | x^4-8x^3+98x^2-648x+1377=0 | | 36m^-4n^-6/4mn^-2p^-4 | | -x^2-100=0 | | 19=4-2m-m+7 | | (2x+4)+(3x-13)=180 | | 20a+25= | | 12-4y=2(y+9) |